Cyberbullying and mental health: past, present and future - Suhans Bansal; Naval Garg; Jagvinder Singh; Freda Van Der Walt (Frontiers in Psychology, 2024)
PurposeCyberbullying has attracted the world's attention, and therefore researchers across the world have contributed to the literature on cyberbullying and mental health. Amongst others, they have conducted bibliometric analyses and associated cyberbullying with various factors but have not determined the impact of cyberbullying on people's mental health. Hence, the aim of this study was to conduct bibliometric analyses of cyberbullying and mental health to analyze the academic performance of the literature on impact of cyberbullying on people's mental health; and to propose future research avenues to make further contributions to this field of study.MethodologySpreadsheets and VOSviewer were used to conduct the bibliometric analysis. The data were extracted from the SCOPUS database which provided an extensive collection of data and journals.FindingsHaving explored the top active countries publishing on the impact of cyberbullying on people's mental health and the academic performance of such research articles by means of a qualitative bibliometric analysis, the results revealed that this research topic is still to be researched extensively. The study also suggests countries/regions where this research topic can be explored further, as well as possible journals for publication of research results, and further studies to be conducted.DiscussionThe literature presents a fragmented view on the impact of cyberbullying on people's mental health. Studies on cyberbullying are limited for the reasons as discussed in this article. Hence, bibliometric analysis was conducted to analyze the performance of academic literature on the impact of cyberbullying on people's mental health; the academic performance of research articles on cyberbullying and mental health; and to make proposals toward a future research agenda.